Preliminary report on two Triassic dicynodonts from Zambia. - Crozier, E. A. (Bernard Price Institute for Palaeontological Research, 1970)
The purpose of this communication is to establish the presence of a species of Stahleckeriid, hitherto known only from India, in the Zambian Triassic N'tawere Formation and to establish the new specific name of the Kannemeyeria specimen also recorded from the same locality. The skulls and some post-cranial material of these two dicynodonts were collected by Mr. James Kitching from the Luangwa Valley, Zambia in 1961. The material comes from Locality 16, of the Lower Fossiliferous Horizon in the N'tawere Formation. One large skull has been assigned to genus and species Rechnisaurus cristarhynchus Roy Chowdhury, 1970. The other skull and the postcranial material has been named Kannemeyeria latirostris sp. nov. One other specimen has been described from this locality, Diademodon rhodesiensis (Brink 1963), which marks it as being of near Cynognathus-zone age.
Main article
Keywords: Dicynodont; Zambia; Triassic